Mediating Instructional Reform: An Examination of the Relationship Between District Policy and Instructional Coaching - Sarah L. Woulfin (SAGE Publishing, 2018)
Districts make and implement policies aiming to improve structures, practices, and outcomes. Instructional coaching has become a popular lever to catalyze instructional improvement efforts. However, many questions remain about the alignment between coaching and reforms. This article draws on coupling theory to analyze the relationship between district policy and instructional coaches' work. Using qualitative case study data from a midsized urban district, I illuminate how coaching reflected three reforms: data use, teacher evaluation, and the Elementary English Language Arts program. I argue that cultural-cognitive, normative, and regulative mechanisms shaped the linkages between each reform and coaches' work in schools. I reveal that structures and routines of coaching matter for coupling policy with practice. These findings have implications for policymakers, scholars, and educators concerned with leaders' roles and responsibilities in enacting instructional reform.